Culture Vitamins – an Arts on Prescription project in Denmark. (May 2019) - Jensen, A
Aims: Four Arts on Prescription (AoP) projects are piloting in Denmark between 2016 and 2019. One of the local authorities delivering the project is Aalborg. The AoP project 'Culture Vitamins' runs for 10 weeks and offers a variety of cultural activities averaging 2.5 workshops per week for participants with mild to moderate depression, stress or anxiety. The study aims to evaluate and explore the potential mental health wellbeing benefits for the participants. Method: A qualitative approach with semi-structured interviews was used and included seven participants who were referred to the project by the local job centre. A thematic approach was applied to analyse the data and a theoretical lens of Salutogenesis was employed to explore the findings. Findings: The findings associated with mental health and the themes that emerged from the data described the participants' subjective experiences and were (1) positive changes, (2) overcoming challenges and being in the 'space' and (3) moving from self-critical to self-caring. The reported mental health benefits were increased energy level, increased self-esteem, more joy in life, less panic attacks, increased motivation, a better understanding of own needs, an increased level of self-care and, in addition, some of the participants said that they felt more aligned to the labour market. Conclusions: The AoP project offered value and meaning for the participants and can be seen as a motivating tool that created access to new experiences and understandings by means of arts engagement. The 'Culture Vitamins' project can be regarded as a catalyst for connecting with inner resources and unlocking some of the barriers that mental ill health has created. The experience has shifted the participants' experience of themselves in the world and initiated their motivation for the future. The 'Culture Vitamins' project offered a positive contribution to public health challenges associated with stress, anxiety and depression of individuals.